The properties of concrete containing rejected foamed concrete as partial sand replacement - Ahmad Lutfi Fajri, Zaidan (2017)
Concrete are a widely used in construction and building material around the world. Today, demand for sand continues to increase for the concrete production. Excessive sand mining in the stream causes negative impact to the river. At the same time, the waste rejected foamed concretes are becoming a serious environmental problem, especially for main cities that lack disposal sites. For environmental protection and sustainable development, a research has to be done on production of concrete from rejected foamed concrete. Firstly, the rejected foamed concrete will be collected from the construction site disposal or factory, then crushed and graded in the range of standard sand. By reusing rejected foamed concrete, it will help in reducing solid waste and environmental problem. The objective is to investigate the effect of rejected foamed concrete on the compressive strength and flexural strength of concrete. The samples would be subjected to water curing process for 7, 28 and 60 days. The findings will highlight the performance of concrete containing rejected foamed concrete as partial sand replacement.